THE ROLE OF THE ONLINE PLATFORM SASTRAARAB.COM IN THE INTERNATIONALIZATION OF ARABIC LITERATURE (A COMPARATIVE LITERATURE STUDY): PERAN MEDIA ONLINE SASTRA ARAB.COM DALAM INTERNASIONALISASI SASTRA ARAB (KAJIAN SASTRA BANDINGAN) - Muhammad Sayyidul Arwan; Ahmad Sirfi Fatoni (Muaddib: Journal of Arabic Language and Literature, 2025)
This article examines the role of the online platform Sastraarab.com in the internationalization of Arabic literature. The study is grounded in the empirical reality that online media has become a vital space for literature enthusiasts worldwide. The main question explored is how Sastraarab.com significantly contributes to this internationalization. Using descriptive analysis, the article draws on primary data from the website and secondary sources such as literature, journal articles, and news media. The findings reveal: (1) Sastraarab.com plays a crucial role by providing Arabic literary discourse within Indonesia’s multiethnic society, simultaneously influencing Indonesian literature; (2) its impact spans intellectual development, translation activities, and media growth, marking it as a major driver of Arabic literature’s reach in Indonesia; (3) internationalizing Arabic literature is essential for fostering intercultural dialogue, breaking stereotypes, enhancing Arab contributions to global civilization, facilitating knowledge exchange, expanding Arabic literary markets, and reinforcing Arab identity in the global era. By promoting Arabic literature internationally, Sastraarab.com helps offer the world richer perspectives on human experience from the Arab world, contributing to a more inclusive and respectful global culture.